Does socioeconomic status account for racial and ethnic disparities in childhood cancer survival?. Issue 20 (20th August 2018) - Kehm, Rebecca D.; Spector, Logan G.; Poynter, Jenny N.; Vock, David M.; Altekruse, Sean F.; Osypuk, Theresa L.
Abstract : Background: For many childhood cancers, survival is lower among non‐Hispanic blacks and Hispanics in comparison with non‐Hispanic whites, and this may be attributed to underlying socioeconomic factors. However, prior childhood cancer survival studies have not formally tested for mediation by socioeconomic status (SES). This study applied mediation methods to quantify the role of SES in racial/ethnic differences in childhood cancer survival. Methods: This study used population‐based cancer survival data from the Surveillance, Epidemiology, and End Results 18 database for black, white, and Hispanic children who had been diagnosed at the ages of 0 to 19 years in 2000‐2011 (n = 31, 866). Black‐white and Hispanic‐white mortality hazard ratios and 95% confidence intervals, adjusted for age, sex, and stage at diagnosis, were estimated. The inverse odds weighting method was used to test for mediation by SES, which was measured with a validated census‐tract composite index. Results: Whites had a significant survival advantage over blacks and Hispanics for several childhood cancers. SES significantly mediated the race/ethnicity–survival association for acute lymphoblastic leukemia, acute myeloid leukemia, neuroblastoma, and non‐Hodgkin lymphoma; SES reduced the original association between race/ethnicity and survival by 44%, 28%, 49%, and 34%, respectively, for blacks versus whites and by 31%, 73%, 48%, and 28%, respectively, for Hispanics versus whites ((log hazard ratio total effect – log hazard ratio direct effect)/log hazard ratio total effect). Conclusions: SES significantly mediates racial/ethnic childhood cancer survival disparities for several cancers. However, the proportion of the total race/ethnicity–survival association explained by SES varies between black‐white and Hispanic‐white comparisons for some cancers, and this suggests that mediation by other factors differs across groups. Abstract : Socioeconomic status mediates the association between race/ethnicity and childhood cancer survival, though to varying degrees across cancers. The proportion of the total effect explained by socioeconomic status varies by race/ethnicity for some cancers. See also pages3975‐8 .